1992
DOI: 10.1038/360591a0
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of dystrophin-related protein

Abstract: Dystrophin-related protein (DRP or 'utrophin') is localized in normal adult muscle primarily at the neuromuscular junction. In the absence of dystrophin in Duchenne muscular dystrophy (DMD) patients, DRP is also present in the sarcolemma. DRP is expressed in fetal and regenerating muscle and may play a similar role to dystrophin in early development, although it remains to be determined whether DRP can functionally replace dystrophin in adult tissue. Previously we described a 3.5-kilobase complementary DNA clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
223
0
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(232 citation statements)
references
References 22 publications
2
223
0
7
Order By: Relevance
“…Dystrophin-related protein or utrophin is considered the autosomal homologue of dystrophin, because it shares extensive sequence homology as well as its size and abundance in muscle (Love et al, 1989;Khurana et al, 1990;Tinsley et al, 1992). Utrophin and dystrophin also share functional properties such as the ability to associate with the dystroglycan complex and bind F-actin (Matsumura et al, 1992;Winder and Kendrick, 1995;Rybakova et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dystrophin-related protein or utrophin is considered the autosomal homologue of dystrophin, because it shares extensive sequence homology as well as its size and abundance in muscle (Love et al, 1989;Khurana et al, 1990;Tinsley et al, 1992). Utrophin and dystrophin also share functional properties such as the ability to associate with the dystroglycan complex and bind F-actin (Matsumura et al, 1992;Winder and Kendrick, 1995;Rybakova et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins of the postsynaptic apparatus implicated in the aggregation of AChRs include utrophin, a synapse-specific homolog of dystrophin (Ohlendieck et al, 1991;Bewick et al, 1992;Tinsley et al, 1992Tinsley et al, , 1994, ␣-and ␤-dystroglycan (Ibraghimov-Beskrovnaya et al, 1992;Fallon and Hall, 1994), and rapsyn (Frail et al, 1988;, thought to link AChRs to the cytoskeleton. Several lines of evidence indicate that the redistribution of AChRs to form postsynaptic aggregates is triggered by the protein agrin, a component of the synaptic basal lamina (BL; McMahan, 1990).…”
mentioning
confidence: 99%
“…The reduced severity of disease in mdx mice is thought to be due to increased expression of utrophin, an autosomal gene product with significant homology to dystrophin. 28,29 In support of this idea, transgenic mice lacking both dystrophin and utrophin have severe muscle disease that more closely resembles Duchenne dystrophy 30,31 and increased transgenic expression of utrophin reduces the muscle pathology in the mdx mouse. 32,34 In a preceding paper, we showed that genetic depletion of utrophin in muscle fibers from mdx mice produces a gene dosedependent increase in the opening probability of single MS channels in recordings from membrane patches.…”
Section: Introductionmentioning
confidence: 75%